Borrowing Constraints, Occupational Choice, and Labor Supply - Bernhardt, Dan; Backus, David (Journal of Labor Economics, 1990)
We introduce borrowing constraints into the life-cycle theory of labor supply and show that they account for observed profiles in consumption, earnings, and hours worked. They can also account for differences in occupational choice across individuals who differ in initial wealth, marital status, or ability. This formalizes several aspects of observed differences in the labor-force behavior of men and women.